Genetic control of resistance to Trypanosoma brucei brucei infection in mice - Síma, Matyáš; Havelková, Helena; Quan, Lei; Svobodová, Milena; Jarošíková, Taťána; Vojtíšková, Jarmila; Stassen, Alphons P M; Demant, Peter; Lipoldová, Marie (PLoS neglected tropical diseases, 2011)
BACKGROUND: Trypanosoma brucei brucei infects livestock, with severe effects in horses and dogs. Mouse strains differ greatly in susceptibility to this parasite. However, no genes controlling these differences were mapped. METHODS: We studied the genetic control of survival after T. b. brucei infection using recombinant congenic (RC) strains, which have a high mapping power. Each RC strain of BALB/c-c-STS/A (CcS/Dem) series contains a different random subset of 12.5% genes from the parental "donor" strain STS/A and 87.5% genes from the "background" strain BALB/c. Although BALB/c and STS/A mice are similarly susceptible to T. b. brucei, the RC strain CcS-11 is more susceptible than either of them. We analyzed genetics of survival in T. b. brucei-infected F(2) hybrids between BALB/c and CcS-11. CcS-11 strain carries STS-derived segments on eight chromosomes. They were genotyped in the F(2) hybrid mice and their linkage with survival was tested by analysis of variance. RESULTS: We mapped four Tbbr (Trypanosoma brucei brucei response) loci that influence survival after T. b. brucei infection. Tbbr1 (chromosome 3) and Tbbr2 (chromosome 12) have effects on survival independent of inter-genic interactions (main effects). Tbbr3 (chromosome 7) influences survival in interaction with Tbbr4 (chromosome 19). Tbbr2 is located on a segment 2.15 Mb short that contains only 26 genes. CONCLUSION: This study presents the first identification of chromosomal loci controlling susceptibility to T. b. brucei infection. While mapping in F(2) hybrids of inbred strains usually has a precision of 40-80 Mb, in RC strains we mapped Tbbr2 to a 2.15 Mb segment containing only 26 genes, which will enable an effective search for the candidate gene. Definition of susceptibility genes will improve the understanding of pathways and genetic diversity underlying the disease and may result in new strategies to overcome the active subversion of the immune system by T. b. brucei.
Keywords: Animals; Genetic Loci; přirozená imunita; Genotype; Female; nemoci hlodavců; Rodent Diseases; mapování chromozomů; ženské pohlaví; Chromosome Mapping; Survival Analysis; Mice; genotyp; Mice, Inbred BALB C; myši; křížení genetické; Trypanosoma brucei brucei; Male; myši inbrední BALB C; Crosses, Genetic; Immunity, Innate; analýza přežití; zvířata; mužské pohlaví; trypanozomóza africká; genetické lokusy; Trypanosomiasis, African